Analysing Buildings from Context to Detail in time. ABCD research method - Zijlstra, Hielkje (2013)
Technology provided the author of this book with the inspiration to develop a more comprehensive research method to assess buildings: Analysing Buildings from Context to Detail in time: ABCD Research Method. Technology, at academic level, should be considered in the analysis of a building. In this book the focus is on construction engineering, the study of the requirements associated with constructing buildings. Providing information on practice is a key element in construction engineering, which is a learning process. Changes are made during the life of a building and they might be made differently if the history and technical aspects of the building were studied in greater detail. Both maintenance and changes require us to understand the building concerned. In essence, a building can be described in detail using the ABCD research method. Experience obtained with other buildings can lead to better considered solutions when designing and building new buildings or intervening in existing buildings. We can recognize layers where changes may have led to interventions in what existed at one time. The ABCD research method is an instrument to show us how changes happened and what the original concepts for the building were. We have to investigate the history of the design and construction of a building to distil this essence.